Proposta de um framework de apoio ao alinhamento dos processos de um programa de mestrado acadêmico com os objetivos da CAPES - Feitosa, Gibson do Carmo (2019)
Periodically the stricto sensu postgraduate programs in Brazil are submitted to the evaluation of the Coordination of Improvement of Higher Education Staff - CAPES, based on pre-defined goals. This evaluation results in a score for each program that can be decisive for the course permanence. In this context, the objective of this research is to present a framework, based on the life cycle of the Business Process Management (BPM) approach and other theoretical models, in order to support the objectives established by CAPES. For that, a bibliographical research and a field research were used. As a research strategy, a case study was developed applied to the process of academic control of the students in a master's degree course at the Federal University of Rio Grande do Norte - UFRN. The Data Collecting was done based on documentary research and interviews. For the treatment of the qualitative data generated, a technique of content analysis was applied, involving the phases of preanalysis, material exploration and interpretation. The first stage of the developed framework corresponds to the planning phase of the BPM life cycle and made it possible to understand the context of the selected postgraduate course, as well as contributing to the identification of the critical objectives of the CAPES evaluation. With the results of the planning stage, it was possible to select the process of academic control of the students to be the object of investigation of ways to align with the objectives of CAPES. The second stage of the proposed framework is based on the phases of process analysis and design of the BPM life cycle. In the analysis phase, were carried out both the mapping and identification of the problems. In turn, a design phase assisted in the identification of the means intended for alignment with the CAPES objectives, when proposing a new version for process. Thus, four management mechanisms were suggested for monitoring and control. The third stage of the framework relates to the phases of implementation and monitoring of the BPM life cycle and did propose the realization of an action plan. The research also resulted in a prototype system, as a result of the experience of all stages of the framework. This prototype was characterized as a support tool in the elaboration of the action plan, contributing to the operationalization of what was proposed in the framework stages. Given the results achieved, the research demonstrated the feasibility of adopting a process approach to generate means of meeting objectives that are considered strategic in the context of an academic master's degree from UFRN.